1995
DOI: 10.1083/jcb.128.5.737
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear localization of the testis determining gene product SRY.

Abstract: Abstract. We have studied the expression of the human SRY protein (termed p27SRY) in two different cell lines by using specific antibodies. Confocal microscopy enabled us to localize p27SRY precisely in the nucleus in a discrete punctuate pattern. Furthermore, through microinjection experiments, we have demonstrated that the localization of the p27SRY protein into the nucleus was an event involving the NH2-terminal part of the high mobility group (HMG) domain. With the help of several synthetic peptides and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
1
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 47 publications
(42 reference statements)
5
97
1
2
Order By: Relevance
“…2A, this antibody detects the expected 34-kDa protein in nuclear extracts and insoluble nuclear fractions (i.e. chromatin and nucleoskeleton) derived from a human NT2D1 cell line, a pluripotent embryonic cell line positive for SRY expression (4,20). In coprecipitation assays, in vitro translated SRY protein (expected size of 27 kDa) associated specifically with SIP-1 fused to GST but not GST alone or with glutathione-Sepharose beads (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…2A, this antibody detects the expected 34-kDa protein in nuclear extracts and insoluble nuclear fractions (i.e. chromatin and nucleoskeleton) derived from a human NT2D1 cell line, a pluripotent embryonic cell line positive for SRY expression (4,20). In coprecipitation assays, in vitro translated SRY protein (expected size of 27 kDa) associated specifically with SIP-1 fused to GST but not GST alone or with glutathione-Sepharose beads (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…SRY encodes a small nuclear protein of 204 residues comprising three distinct domains, with a central domain of about 78 amino acids called the high mobility group (HMG) 1 box. This central domain includes a nuclear localization signal (4), and in vitro studies of the human SRY protein have demonstrated its sequence-specific DNA binding through this HMG box (5). To date, no function has been ascribed to the regions of the human SRY protein outside the HMG box, whereas in mouse Sry, the Cterminal part of the protein can function as a transcriptional activator (6).…”
mentioning
confidence: 99%
“…between 25 and 36 dpc, gonads were not separated from mesonephroi. Wilhelm et al, 2005), or in human cells and tissues (Poulat et al, 1995;Salas-Cortés et al, 1999).…”
Section: Subcellular Localization Of the Proteinmentioning
confidence: 99%
“…Until now, SRY antibodies were only available against mouse and human proteins (Wilhelm et al, 2005;Bradford et al, 2007;Poulat et al, 1995;Salas-Cortés et al, 1999). In humans, the first SRY antibody was polyclonal and produced against a 17 amino-acid peptide located in the Nterminal part of the protein (residues 40 to 56).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation